Atmospheric Drag, Occultation 'N' Ionospheric Scintillation (ADONIS) mission proposal: Alpbach Summer School 2013 team orange - Hettrich, Sebastian; Kempf, Yann; Perakis, Nikolaos; Górski, Jędrzej; Edl, Martina; Urbář, Jaroslav; Dósa, Melinda; Gini, Francesco; Roberts, Owen W.; Schindler, Stefan; Schemmer, Maximilian; Steenari, David; et al. (Journal of Space Weather and Space Climate, 2016)
The Atmospheric Drag, Occultation ‘N’ Ionospheric Scintillation mission (ADONIS) studies the dynamics of the terrestrial thermosphere and ionosphere in dependency of solar events over a full solar cycle in Low Earth Orbit (LEO). The objectives are to investigate satellite drag with in-situ measurements and the ionospheric electron density profiles with radio occultation and scintillation measurements. A constellation of two satellites provides the possibility to gain near real-time data (NRT) about ionospheric conditions over the Arctic region where current coverage is insufficient. The mission shall also provide global high-resolution data to improve assimilative ionospheric models. The low-cost constellation can be launched using a single Vega rocket and most of the instruments are already space-proven allowing for rapid development and good reliability. From July 16 to 25, 2013, the Alpbach Summer School 2013 was organised by the Austrian Research Promotion Agency (FFG), the European Space Agency (ESA), the International Space Science Institute (ISSI) and the association of Austrian space industries Austrospace in Alpbach, Austria. During the workshop, four teams of 15 students each independently developed four different space mission proposals on the topic of “Space Weather: Science, Missions and Systems”, supported by a team of tutors. The present work is based on the mission proposal that resulted from one of these teams’ efforts. publishedVersion